The effects of cold water ingestion, pre- and during exercise, on running performance of male recreational runners - Amargo, Bjorn Joshua G.; Valleser, Christian Wisdom M. MSHMS (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
This study aims to determine the effects of cold water ingestion, as a cooling strategy to improve running performance and exercise experience. This specifically investigated the effects on the overall running time, skin temperature, and rating of perceived exertion (RPE) when ingesting cold water compared to room temperature water. Ten (10) male, young adult recreational runners participated in this study. The experiment was done using a crossover design, which consists of two testing days. The participants ran a total of 2 kilometers on each lest day. ingesting either Cold Water (CW) or Room Temperature Water (RT). Skin temperature. RPE. and the overall running time of each participant was recorded on both testing days to compare and analyze the differences when ingesting cold water versus room temperature water 1 he data showed a significant decrease in the overall running times of the participants, with a mean of 530.4 seconds (a = 48.7) in the CW protocol compared to a mean of 585.5 (q = 64.9) in the RT protocol. There is also a significant difference in skin temperature during pre-exercise, with an effect size of-1.66 (p < 0.001) implying a significantly greater decrease in skin temperature when ingesting cold water. However, there are no significant differences in skin temperature mid- and post-exercise. There are also no significant differences in RPE between the two test protocols. The findings in the study imply that with the same perceived effort exerted, cold water ingestion can improve running performance by helping the individuals run at a faster pace for a longer duration resulting in faster completion times. This study also proves that cold water ingestion helps in lowering skin temperature pre-exercise, but also provides benefits on RPE and thermal sensation during exercise.
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Exercise; Drinking water; Running; Runners (Sports)